1
$\begingroup$

I was trying to prove some of the results related to beta function and I came across this step

Therefore, $$\frac{B(m+1,n)}{m}=\frac{B(m,n+1)}{n}=k,\quad\mathrm{say}\quad\ldots(i)$$ This yields $$k=\frac{B(m+1,n)+B(m,n+1)}{m+n}$$

Can anyone tell me how they got the value of $k$? Thanks in advance.

$\endgroup$
0
$\begingroup$

From the first equation, we get $km=B(m+1,n)$ and $kn=B(m,n+1)$. Thus, $$k=\frac{k(m+n)}{m+n}=\frac{km+kn}{m+n}=\frac{B(m+1,n)+B(m,n+1)}{m+n}$$

$\endgroup$
0
$\begingroup$

The first equation equates three different expresssion. We may pick any two to make an equation. Take the first and last, with a slight rearrangement:

$B(m+1,n) = m k$

then the second and last:

$B(m,n+1) = n k$

Now, just add these two equations I just wrote. The final step should be obvious.

$\endgroup$

Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.